The role of the HGF/c-MET signalling pathway in cellular crosstalk during chronic liver injury - Pasic, Sara (Curtin University, 2023)
The HGF/c-MET signalling pathway is known to be antifibrotic in the liver. However, its influence on liver progenitor cell (LPC) and hepatic stellate cell (HSC) communication during chronic liver disease (CLD) is unknown. Here, CRISPR/Cas9 technology was utilised to create a c-MET knockout LPC line, which altered LPC biology and diminished the HSC-regulatory potential of LPCs. These findings suggest that HGF/c-MET signalling is important for maintaining LPC biology and regulating HSC behaviour in CLD.